2018
DOI: 10.1002/marc.201800064
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Reactions for Surface Modification

Abstract: Modification of material surfaces with polymers is an effective method to develop applicable polymer-material composites. Recently, multicomponent reactions (MCRs) have found their roles in advanced polymer chemistry and applied in surface modification. In this mini review, recent results of MCRs for surface modification are summarized, including the utilization of MCRs as coupling tools to link polymers on material surfaces, and polymers containing multicomponent structures for surface modification. The uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…In addition, surface functionalization of inorganic substrate materials can also be accomplished by a one‐step KF reaction. [ 115–117 ] The preparation of functional polymers with AIE properties through KF reaction was first presented by Long et al. [ 118 ] They showed that KF reaction can be used as a clean coupling reaction for fabrication of functional luminescent copolymers with economical, green, and high‐yield.…”
Section: Fabrication Of Fluorescent Copolymers With Aie Feature Throumentioning
confidence: 99%
“…In addition, surface functionalization of inorganic substrate materials can also be accomplished by a one‐step KF reaction. [ 115–117 ] The preparation of functional polymers with AIE properties through KF reaction was first presented by Long et al. [ 118 ] They showed that KF reaction can be used as a clean coupling reaction for fabrication of functional luminescent copolymers with economical, green, and high‐yield.…”
Section: Fabrication Of Fluorescent Copolymers With Aie Feature Throumentioning
confidence: 99%
“…For the prompt development of the post-polymerization approach in polymer science, click reactions provide a reliable synthesis platform. Thus, a wide range of click-type reactions have been integrated with polymer synthesis, including thiol–ene, nucleophile–epoxides, 1,3-dipolar cycloaddition of organic azides and terminal alkynes, , multicomponent reactions, and activated ester–amine reactions . Among the available click-type reactions in polymer synthesis, activated ester–amine chemistry constitutes the most ideal approach not only in polymer chemistry but also in material chemistry due to the easy handling of the reactions involving functional amines.…”
Section: Introductionmentioning
confidence: 99%
“…the reactions included three or more reactants, are attractive as simple methods of preparation of organic compounds with the great molecular diversity. They can be useful as effective synthetic protocols for obtaining the new libraries of compounds with the potential biological activity [10][11][12][13][14][15][16], natural products [10,[14][15][16][17], agrochemicals [10,18], substances for the electronics [19,20], and also unique polymeric materials [21][22][23]. MCRs are characterized by higher atom economy and require less efforts comparing with the laborious stepby-step procedures of organic synthesis.…”
Section: Introductionmentioning
confidence: 99%